Decarbonization Strategy towards Net Zero Emission for International Shipping on International Shipping Routes in Indonesian Archipelago Sea Lanes - Idris Hadi; Lin Yola; Aldy Syahrihaddin Hanifa; Muhammad Hanief Muzhaffar (International Journal of Technology)
International Maritime Organization (IMO) has mandated measures to address greenhouse gas emissions from international shipping. Therefore, this study aims to develop a novel initiative for collaborative decarbonization strategies involving ship operators, regulators, and the broader maritime community, as part of Indonesian efforts to mitigate carbon emissions in the shipping sector. A case study was conducted focusing on international vessels transiting through Indonesian Archipelagic Sea Lanes (ALKI). The qualitative method supported by quantitative data analysis was applied and data were collected through direct interviews with relevant stakeholders, including business actors, ship crews (operators), maritime authorities (government representatives), and coastal communities. These findings estimated that carbon emissions from 12,189 ships passing through ALKI-II amount to approximately 3,110,023 tons of CO2 annually, with additional emissions from ships in ALKI-I and ALKI-III. In light of the absence of a comprehensive decarbonization strategy for the Indonesian maritime sector, this study proposes a framework for reducing carbon emissions toward achieving net-zero emissions for the thousands of international ships transiting ALKI each year. This proposed strategy can be incorporated into the Indonesian Nationally Determined Contribution (NDC) report to the United Nations, potentially attracting funding through grants or global Environmental, Social, and Governance (ESG) funds. This funding would support the sustainable implementation of carbon management strategies, advancing the objective of net-zero emissions.